SEJARAH LEMBAGA PENDIDIKAN ISLAM (MADRASAH) DAN PERKEMBANGANNYA DI INDONESIA - Ach. Taufik Hidayatullah; Jalaludin Mahalli; Ahmad Ainul Yaqin (Universitas Sains dan Teknologi Komputer, 2022)
Madrasah Ibtidaiyah is a formal Islamic educational institution in Indonesia which is under the auspices of the Ministry of Religion. The existence of Madrasah Ibtidaiyah today is inseparable from the history of madrasas developed by Islamic countries in the Middle East, to Islamic education that existed in Indonesia long before independence and to the present. At the beginning of its development, Madrasah was an Islamic educational institution with the establishment of the Nizhamiyah Madrasa in Baghdad when the vizier of the Bani Seljuq Nizhamul Muluk in the 5th century Hijriyah. Then Islamic education entered Indonesia, which at first only used the classical system such as teaching in suraus or mosques and the Islamic boarding school system. Several Islamic educational institutions in Indonesia have reformed the classical education system into a madrasa system (class). Madrasah Ibtidaiyah is one of the products of renewal of Islamic education in Indonesia which is devoted to basic education. After the independence of the Republic of Indonesia, madrasah Ibtidaiyah became educational institutions that taught Islamic religious knowledge as the subject of teaching, and also taught general knowledge at least; Indonesian, counting and reading and writing Latin letters for lower level madrasas (Madrasah Ibtidaiyah).